2008
DOI: 10.1002/ptr.2528
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Peganum harmala or its β‐carboline alkaloids on certain antibiotic resistant strains of bacteria and protozoa from poultry

Abstract: In the present study the antimicrobial potential of various extracts from 12 medicinal plants has been investigated in vitro on multiple antibiotic resistant pathogens and some selected protozoa isolated from poultry. The initial examination was performed on E. coli (n = 10) using disc and agar well diffusion assays. Only two plants, Peganum harmala (seeds) and Eucalyptus globulus (leaves) showed positive responses. The active extracts were also investigated against an additional 19 bacteria and the clonal cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
40
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(44 citation statements)
references
References 24 publications
4
40
0
Order By: Relevance
“…Cell cycle analysis suggests that harmine does not induce apoptosis in Leishmania donovani promastigotes although playing a part in the cell division stage [17] . In another study, harmine was found to be effective against bacteria and protozoa [18,19] . The potential induction of a programmed cell death in Trypanosoma b. brucei by harmine was studied by measuring DNA fragmentation and changes in potential of mitochondrial membrane.…”
Section: Effect Of Harmine Against Microorganismsmentioning
confidence: 97%
“…Cell cycle analysis suggests that harmine does not induce apoptosis in Leishmania donovani promastigotes although playing a part in the cell division stage [17] . In another study, harmine was found to be effective against bacteria and protozoa [18,19] . The potential induction of a programmed cell death in Trypanosoma b. brucei by harmine was studied by measuring DNA fragmentation and changes in potential of mitochondrial membrane.…”
Section: Effect Of Harmine Against Microorganismsmentioning
confidence: 97%
“…Within recent years a trend towards non-chemotherapeutic alternative means has been set in the combat of histomonosis. Despite this awareness there is still only a limited number of in vitro studies on the effects of natural compounds on H. meleagridis available (Zenner et al, 2003;Grabensteiner et al, 2007Grabensteiner et al, , 2008Hauck & Hafez, 2007;Arshad et al, 2008;van der Heijden & Landman, 2008a). The situation is similar when it comes to evaluating the impact of natural compounds on histomonosis in vivo (Duffy et al, 2004(Duffy et al, , 2005Hafez & Hauck, 2006;Grabensteiner et al, 2008;van der Heijden & Landman, 2008b).…”
Section: Introductionmentioning
confidence: 99%
“…Lemon grass (Cymbopogon citratus Stapf) affects the sympathetic nervous system, reducing stress (Negrelle & Gomes, 2007). Although some researchers investigated the use of phytotherapy in poultry production, most are related to animal nutrition (Wenk, 2003;Hashemi & Davoodi, 2010) and microbiological control (Arshad et al, 2008;Lourenço et al, 2013). This study aimed at evaluating the use of lemon grass (Cymbopogon citratus Stapf) to reduce broiler pre-slaughter stress.…”
Section: Introductionmentioning
confidence: 99%